ANALISIS FAKTOR-FAKTOR STRATEGIS DALAM PENGEMBANGAN SEKTOR PARIWISATA DI PROVINSI LAMPUNG - -, Subhi (Jurnal Manajemen dan Keuangan, 2012)
The purpose of this article is trying to answer the question of influence between the introduction and knowledge with public perceptions, between the interests and influence the public perception is shared between the introduction, knowledge of and interest on the public perception?. This paper attempts to provide data to local authorities, business community and general public who wish to obtain information to determine the policy and developing a starategi and services of the tourism sector. The results of the questionnaire, namely the distribution of data processing description of the tourism sector in Bandar Lampung to variable levels of recognition is not good, fairly good knowledge and interest of the public good and public perception is quite good. Based on the results of statistical testing inferesia have a significant effect of the introduction of public perception in Bandarlamung. Thus the current problems of the introduction has not been too important to be increased, because the public perception is positive predominantly determined by other factors such as knowledge, interests, moderators and others. Persons level of knowledge and public perception will be influenced by the level of knowledge of tourism in general and in particular, for the people in Bandarlampung. Conclusion: pay attention to the findings of the study 1) the introduction, knowledge and interest is recommended to be increased through various policies. Conducted a policy of planned, purposeful, continuous and integrated, which will ultimately have a positive impact that public perception in line with expectations and demands of its main organizational performance needs of local government, 2) have formulated the concept of recognition, knowledge and interest in the perception of the more obvious it is not the introduction of obscure meaning, knowledge and interests with managements perception of tourism which has been frequently used to describe the management of the ambiguous state apparatus through the Department of Tourism And conceptually, these words have different meanings, 3) the results of this study should be followed up with further research or studies in-depth and focused in order to formulate a model pepengenalan, knowledge and effective public interest against the public perception towards the environmental performance of government agencies. These results serve as guidelines in the interest of fostering an interest and perception of performance in accordance with the expectations of the organization, 4) all cross-cutting is expected to be directed by government policy to support the tourism sector and tourism as the flagship product in the province of Lampung.Keywords : Perception, recognition, knowledge and interests.